English Teachers’ Perspectives of Learner Autonomy in Online Reading Comprehension in Times of the COVID-19 Pandemic - Stevani, Margaret; Ginting, Fiber Yun Almanda (JOURNAL OF TEACHING AND LEARNING IN ELEMENTARY EDUCATION (JTLEE), 2022)
The objectives of this research were focused on English teachers’ perspectives on learner autonomy and to what extent English teachers felt their learners were autonomous in online reading comprehension in times of the COVID-19 pandemic. These research questions were answered by using observation, interview, and Likert-scale questionnaire in the form of qualitative method. The sample of this study was 26 English teachers in 4 elementary schools and 5 junior high schools in North Sumatra, Indonesia. The results of the study showed some points on learner autonomy, such as: (1) the importance of learner autonomy, (2) the way English teachers promoted learner autonomy, (3) the challenges and responsibilities of English teachers to implement learner autonomy, (4) English teachers’ observation to learners’ autonomy in online reading comprehension, (5) learners’ activities in online reading comprehension strategy, and (6) English teachers’ preparation in online reading comprehension class. This research concluded that the degree of learners’ autonomy during the pandemic was higher rather than before the COVID-19 pandemic due to some reasons.